Budget of tropospheric ozone during TOPSE from two chemical transport models - Emmons, L. K.; Hess, P.; Klonecki, A.; Tie, X.; Horowitz, L.; Lamarque, J. F.; Kinnison, D.; Brasseur, G.; Atlas, E.; Browell, E.; Cantrell, C.; Eisele, F.; et al. (Journal of Geophysical Research: Atmospheres, 2003)
The tropospheric ozone budget during the Tropospheric Ozone Production about the Spring Equinox (TOPSE) campaign has been studied using two chemical transport models (CTMs): HANK and the Model of Ozone and Related chemical Tracers, version 2 (MOZART-2). The two models have similar chemical schemes but use different meteorological fields, with HANK using MM5 (Pennsylvania State University, National Center for Atmospheric Research Mesoscale Modeling System) and MOZART-2 driven by European Centre for Medium-Range Weather Forecasts (ECMWF) fields. Both models simulate ozone in good agreement with the observations but underestimate NOx. The models indicate that in the troposphere, averaged over the northern middle and high latitudes, chemical production of ozone drives the increase of ozone seen in the spring. Both ozone gross chemical production and loss increase greatly over the spring months. The in situ production is much larger than the net stratospheric input, and the deposition and horizontal fluxes are relatively small in comparison to chemical destruction. The net production depends sensitively on the concentrations of H2O, HO2 and NO, which differ slightly in the two models. Both models underestimate the chemical production calculated in a steady state model using TOPSE measurements, but the chemical loss rates agree well. Measures of the stratospheric influence on tropospheric ozone in relation to in situ ozone production are discussed. Two different estimates of the stratospheric fraction of O3 in the Northern Hemisphere troposphere indicate it decreases from 30-50% in February to 15-30% in June. A sensitivity study of the effect of a perturbation in the vertical flux on tropospheric ozone indicates the contribution from the stratosphere is approximately 15%.